THE ROLE OF EMOTIONAL INTELLIGENCE AS MODERATION BETWEEN THE INFLUENCE OF FORENSIC ACCOUNTING AND INVESTIGATION AUDIT ON BEHAVIOR OF CORRUPTION - Rusli, Yohanes Mardinata; Asih, Yuli; Wijaya, Daniel (Indonesian Journal of Accounting and Governance, 2023)
This study purpose to examine the effect of forensic accounting on corrupt behavior and the effect of investigative audits on corrupt behavior. The role of Emotional Intelligence as a moderation between The Influence of Forensic Accounting on Corrupt Behavior. The Role of Emotional Intelligence as a moderator between the influence of Audit Investigation on Corrupt Behavior. With using multiple regression analysis. The researcher concludes that there is an effect of Forensic Accounting and Investigative Audit on Corrupt Behavior and the role of Emotional Intelligence as a moderator between the influence of Forensic Accounting and Investigative Audit on Corrupt Behavior.